Analisis Implementasi Kurikulum Merdeka Pada Mata Pelajaran Ekonomi Di SMAN 1 Bengkulu - Deanti Putri Rania; Sazili Sazili; Zufiyardi Zufiyardi; Hilyati Milla; Rossa Ayuni (Universitas Dehasen Bengkulu, 2024)
This research aims to find out: (1) planning for the independent curriculum in economics subjects at SMAN 1 Bengkulu (2) implementation of the independent curriculum for economics subjects at SMAN 1 Bengkulu (3) evaluation of the independent curriculum for economics subjects at SMAN 1 Bengkulu. This research was conducted at SMAN 1 Bengkulu using a qualitative descriptive research approach and type. Data was collected using interview, observation and documentation methods. The data analysis used in this research includes data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data using triangulation, namely source triangulation and technical triangulation. The results of research conducted at SMAN 1 Bengkulu are: (1) in planning learning, the teaching tools used by the teacher are appropriate and refer to the teaching tools provided by the Ministry of Education and Culture (2) the learning carried out by the teacher tries to refer to the learning principles in the independent and existing curriculum. at the developing stage with the consideration that the learning carried out is centered on students and the accuracy of the learning methods used (3) evaluation is carried out by referring to the assessment principles launched by the Ministry of Education and Culture.